Zircon in amphibolites from Naxos, Aegean Sea, Greece: origin, significance and tectonic setting. (26th December 2016) - Bolhar, R.; Ring, U.; Ireland, T. R.
Abstract: We report U–Pb zircon ages of c . 700–550 Ma, 262–220 Ma, 47–38 Ma and 15–14 Ma from amphibolites on Naxos Island in the Aegean extensional province of Greece. The zircon has complex internal structures. Based on cathodoluminescence response, zoning and crosscutting relationships a minimum of four zircon growth stages are identified: inherited core, magmatic core, inner metamorphic (?) rim and an outer metamorphic rim. Trace element compositions of the amphibolites suggest igneous differentiation and crustal assimilation. Zircon solubility as a function of saturation temperatures, Zr content and melt composition indicates that the zircon did not originally crystallize in the mafic bodies but was inherited from felsic precursor rocks, and subsequently assimilated into the mafic intrusives during emplacement. Zircon inheritance is corroborated by the complex, xenocrystic nature of the zircon in one sample. Ages of c . 700–550 Ma and 262–220 Ma are assigned to inherited zircon. Available geochemical data suggest that the 15–14 Ma metamorphic rims grew in situ in the amphibolites, corresponding to a high‐grade metamorphic event at this time. However, the geochemical data cannot conclusively establish if the c . 40 Ma zircon rims also grew in situ, or whether they were inherited along with the xenocrystic cores. Two scenarios for emplacement of the mafic intrusives are discussed: (i) Intrusion during late‐Triassic to Jurassic ocean basin development of the Aegean realm, in which case the 40 Ma zircon rims would have grown in situ, and (ii) emplacement in the Miocene as a result mafic underplating during large‐scale extension. In this case, only the 15–14 Ma metamorphic outer rims would have formed in situ in the amphibolitic host rocks.